MANAJEMEN DAN KEPEMIMPINAN PENDIDIKAN ISLAM - Ummah Karimah (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2015)
Abstract: Man is essentially a leader on this earth (khalifa fil ard), but when the man had been in charge of all types of professions and demanded their sense of responsibility, then that is where it is from among humans as a leader was chosen to be the figure of a single leader. Being a leader is not only easy matter, because in addition to the need to have the capability must also have the courage, in the sense of daring to confront and provide insight and solutions to various problems faced by mankind. Leadership in education can be interpreted as a human figure can become a driving force in humanizing, for the purpose of education is humanizing. This article tries to illustrate a message of Caliph Ali is, when asked by a friend to the critical question of "why when Muslims led by the Caliph Ali is unrest among Muslims, whereas when it is led by the Caliph before any peace-peace" then Sayyidina Ali replied "when Caliph before I lead, his people are like me, whereas when I became Caliph and became a leader, yes ummatnya like these guys are like the kerebutan." The message of the illustrations as if that one side of his people blame their leaders, while on the other side of a leader also blamed the people he leads. This article attempts to provide a middle way that the error could have been between them, but were forbidden to blame, which must be addressed is the management leadership, so that when it is applied in the Islamic leadership will be born a superior management of Islamic education and productive.